Intergenerational Support in a Daily Context - Fingerman, Karen L. (Gerontologist, 2016)
PURPOSE OF THE STUDY: Using retrospective global reports, studies have found that middle-aged adults in the United States provide intermittent support to their aging parents and more frequent support to grown children. To date, studies have not examined support middle-aged adults provide to different generations on a daily basis. Daily support may include mundane everyday exchanges that may (or may not) affect well-being. DESIGN AND METHODS: Middle-aged adults (N = 191, mean age 55.93) completed a general interview regarding family ties, followed by interviews each day for 7 days (N = 1,261 days). Daily interviews assessed support (e.g., advice, emotional, practical help) participants provided each grown child (n = 454) and aging parent (n = 253). Participants also reported daily mood. RESULTS: Most participants provided emotional support (80%), advice (87%), and practical help (69%) to a grown child and also provided emotional support (61%) and advice (61%) or practical help (43%) to a parent that week. Multilevel models confirmed generational differences; grown children were more likely to receive everyday support than parents. Providing support to grown children was associated with positive mood, whereas providing support to parents was associated with more negative mood. IMPLICATIONS: Daily intergenerational support was more common than studies using global reports of support have found. Some daily support may be fleeting and not stand out in memory. The findings were consistent with the intergenerational stake hypothesis, which suggests middle-aged adults are more invested in their grown children than in their parents. Nonetheless, middle-aged adults were highly involved with aging parents.